MENINGKATKAN KETRAMPILAN KOMUNIKASI INTERPERSONAL SISWA MELALUI LAYANAN KLASIKAL DENGAN MEDIA GROUP WHATSAAPP - ELLY AGUSTIN FITRIANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This type of research is classroom action research with the number of research subjects is 32 children with the aim of improving students' interpersonal communication and knowing the classical guidance services carried out by Guidance Counseling teachers at Mts Negeri 4 Gunungkidul. Communication is one of the important elements in learning. Personal Communication emphasizes student activities in learning that are full of responsibility for success in learning. Students who have good communication will easily accept the subject matter given by the teacher. Good communication can be shown by the ability to solve problems faced with behavior. With changes in behavior, students also have an increase in thinking, assuming that in learning they must be able to be independent without relying on help from others and also not relying on learning from the teacher alone, but learning can also be from print, electronic, natural, or other media. other. The results of the study the increase in children's personal communication in the second cycle in the first group was 22.1%. With an average value of 82.05, this means that children's communication is very good, where 5 children have scores ranging from 70-80 including the medium category and 6 children are already above 80 which are included in the high category of child communication. the increase in children's communication in the second cycle in the second group was 25.1%. With an average score of 85.45, this means that children's communication is very good, where 4 children have scores ranging from 70-80 including the medium category and 7 children are already above 80 which are included in the high communication category. the increase in children's communication in the second cycle in the third group was 21.7%. With an average value of 88, this means that children's communication is very good, where 10 children are already above the value of 80 which is included in the category of high personal communication. ABSTRAKJenis penelitian ini adalah penelitian tindakan kelas dengan jumlah subyek penelitian adalah 32 anak dengan tujuan untuk meningkatkan komunikasi interpersonal siswa dan mengetahui layanan bimbingan klasikal yang dilakukan oleh guru Bimbingan Konseling di Mts Negeri 4 Gunungkidul. Komunikasi merupakan salah satu unsur yang penting dalam pembelajaran. Komunikasi Personal menekankan pada aktivitas siswa dalam belajar yang penuh tanggung jawab atas keberhasilan dalam belajar. Siswa yang memiliki komunikasi yang baik akan mudah menerima materi pelajaran yang diberikan guru. Komunikasi yang baik dapat ditunjukkan dengan adanya kemampuan dapat menyelesaikan masalah yang dihadapi dengan tingkah laku. Dengan adanya perubahan tingkah laku maka siswa juga memiliki peningkatan dalam berfikir, menganggap bahwa dalam belajar harus bisa mandiri tanpa mengandalkan bantuan dari orang lain terus dan juga tidak menggantungkan belajar dari guru saja, tapi belajar juga bisa dari media cetak, elektronik, alam, atau yang lainnya. Hasil penelitian kenaikan komunikasi personal anak pada siklus yang kedua di kelompok pertama sebesar 22,1 %. Dengan nilai rata- rata sudah 82,05 hal ini berarti komunikasi anak sudah sangat baik, dimana 5 anak nilai berkisar antara 70-80 termasuk katagori sedang dan 6 anak udah diatas nilia 80 yang termasuk dalam katagori komunikasi anak yang tinggi. kenaikan komunikasi anak pada siklus yang kedua di kelompok kedua sebesar 25,1 %. Dengan nilai rata- rata sudah 85,45 hal ini berarti komunikasi anak sudah sangat baik, dimana 4 anak nilai berkisar antara 70-80 termasuk katagori sedang dan 7 anak udah diatas nilia 80 yang termasuk dalam katagori komunikasi yang tinggi. kenaikan komunikasi anak pada siklus yang kedua di kelompok ketiga sebesar 21,7 %. Dengan nilai rata- rata sudah 88 hal ini berarti komunikasi anak sudah sangat baik, dimana 10 anak sudah diatas nilai 80 yang termasuk dalam katagori komunikasi personal yang tinggi.